Supplementary Effect of Different Levels of Nano Zinc Oxide on Zinc Bioavailability and Blood Metabolites in Lambs - Singh, K K; Maity, S B; Maity, A (Indian Journal of Animal Nutrition, 2019)
Twenty five Jalauni male lambs (average body weight = 4.5 kg, age 35 d) were randomly divided into 5 groups of 5 animals each. All the lambs were maintained on basal ration comprising grass hay and concentrate mixture (Maize grain, mustard cake and common salt in the ratio of 64: 35: 1). The group G1 served as control supplemented with 40 ppm zinc from ZnO while the lambs in groups G2, G3, G4 and G5 were supplemented with 40, 30, 20, 10 ppm Zn from nano ZnO (nZnO 30 nm) in the concentrate mixture over and above the basal ration (24.12 ppm) for a period of 150 d. Results indicated no difference in the intake and digestibility of nutrients amongst groups. The Zn intake was higher (P<0.05) in group G1 and G2 as compared to groups G3 to G5. A similar trend was also observed for faecal and urinary Zn excretion which was higher (P<0.05) in group G1 as compared to groups G2, G3, G4 and G5.that led to higher Zn retention (2.01 and 1.88 mg/d) in groups G2and G3 as compared to groups G1, G4 and G5 (1.50, 1.40 and 1.33 mg/d) and absorption was higher (P<0.05) in nZnO supplemented lambs in comparison to ZnO supplemented lambs (G1). The blood metabolites were within the normal physiological range except that plasma Zn concentration was higher (P<0.05) in nZnO supplemented lambs. Hence, nZnO improved (P<0.05) Zn availability in lambs. Thus, nZnO could be a better source of Zn supplementation at a supplementary level of 20 ppm.